2020
DOI: 10.7717/peerj.9880
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the transcriptome-wide m6A methylome in preeclampsia and healthy control placentas

Abstract: N6-methyladenosine (m6A) is the most prevalent modification in eukaryotic mRNA and potential regulatory functions of m6A have been shown by mapping the RNA m6A modification landscape. m6A modification in active gene regulation manifests itself as altered methylation profiles. The number of reports regarding to the profiling of m6A modification and its potential role in the placenta of preeclampsia (PE) is small. In this work, placental samples were collected from PE and control patients. Expression of m6A-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…There were 4,014 differentially m6A peaks, corresponding to 2,144 genes, and each gene was associated with at least one or more m6A peaks. The distribution of m6A peaks appeared in the CDS, which was also consistent with other diseases such as cancer (Zhang et al, 2020b), traumatic brain injury (Yu et al, 2020), and preeclampsia (Wang et al, 2020a). After PNI, these m6A peaks preferentially located at the start codons (19.17 vs. 17.49%), and there was a decreasing trend in the CDS (66.75 vs. 68.49%).…”
Section: Discussionsupporting
confidence: 76%
“…There were 4,014 differentially m6A peaks, corresponding to 2,144 genes, and each gene was associated with at least one or more m6A peaks. The distribution of m6A peaks appeared in the CDS, which was also consistent with other diseases such as cancer (Zhang et al, 2020b), traumatic brain injury (Yu et al, 2020), and preeclampsia (Wang et al, 2020a). After PNI, these m6A peaks preferentially located at the start codons (19.17 vs. 17.49%), and there was a decreasing trend in the CDS (66.75 vs. 68.49%).…”
Section: Discussionsupporting
confidence: 76%
“…The number of reports regarding the profiling of m6A modification and its potential role in the placenta of PE is small. Several studies have investigated the clinical features in PE patients and healthy controls and found no difference in maternal age in the whole group [ 17 , 18 ]. Currently, no study has analysed the correlation between maternal age and m6A levels in PE patients, and our results need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Given the indispensable function of RNA m6A modification in various bioprocesses, it is reasonable to speculate that deregulation of m6A modification may also be associated with PE. Recent studies showed that METTL3 and METTL14 were upregulated in PE and verified that the significant increase in HSPA1A mRNA and protein expression was regulated by m6A modification, suggesting that m6A plays a key role in the regulation of gene expression [ 18 ]. Increased METTL3 expression and m6A RNA methylation were also observed by Taniguchi et al, and they suggested that aberrant m6A modification may contribute to trophoblast dysfunction in PE [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al mapped the m 6 A modification profile of preeclampsia placenta and found that METTL3 and METTL14 were up-regulated in preeclampsia. Differential m 6 A-modified transcripts are primarily associated with the nitrogen compound metabolic process, positive regulation of vascular-associated smooth muscle cell migration, and several cancer-related pathways ( Wang et al, 2020a ). Li et al also found that the reduced methylation of m 6 A in RSA villous may inhibit the invasion of villous cells and lead to RSA ( Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Differential m 6 A-modified transcripts are primarily associated with the nitrogen compound metabolic process, positive regulation of vascular-associated smooth muscle cell migration, and several cancer-related pathways ( Wang et al, 2020a ). Li et al also found that the reduced methylation of m 6 A in RSA villous may inhibit the invasion of villous cells and lead to RSA ( Wang et al, 2020a ). However, whether m 6 A modification can lead to RSA and its exact mechanisms still need to be proved by a large number of studies.…”
Section: Introductionmentioning
confidence: 99%